Development Orientation: European Change in Max Weber's Perspective - Ismail, Ashari (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Max Weber's thesis that announced the development of European change, due to Protestantism, which is closely related to capitalism, is the pursuit of maximum economic profit with a long-term ownership orientation. Protestantism is considered to have an inherent logical dynamic with the doctrine of being the spirit of pursuing economic profit. This study aims to examine Weber's thoughts in the context of development in Europe, and to provide criticism of the development orientation that arises from this thought. This study is library research, with a qualitative exploratory descriptive research type, which seeks to describe new findings from a research problem. Such an understanding, through a literature review with a library study method, is understood the criticism that capitalism should be a rational occupational conscience, about a work ethic, driven by the enjoyment of a material value of work, due to the development of liberalization and ownership. Upholding capital as an element of rationalization, is a strong spirit of the emergence of capitalism and the rejection of the irrational elements of work based on religious morality. In this regard, rational occupation, based on freedom of creativity, private ownership and productive efforts are the basic reasons for the birth of capitalism. This research can be a reference, especially regarding the spirit of capitalism and rationalization, offering a unique perspective on the social, economic, and cultural transformations of that era.